SIMBOL LITERAL DAN KONTEKSTUAL DALAM MANTRA JAWA AJI SEDULURAN - Teguh Budiharso (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2014)
In this article, the literal and contextual symbols of Aji Seduluran, a Javanese magical formula were examined. Twelve versions of the -˜mantra ’ -Hindu and Islamic- were analyzed by using discourse analysis. The purpose was to understand the meanings of the symbols, the relations among them, and interpret those symbols according to the Javanese social and philosophical contexts. Based on their scope the symbols may be grouped into: 1) language universal symbols and 2) language culturally bound symbols. The results indicated that the symbols might be classified into three categories: a) spiritual symbols; b) social and moral symbols; 3) symbols of tradition. The symbols were also proven to be universal.